Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s12603-015-0470-7
|View full text |Cite
|
Sign up to set email alerts
|

Change in red blood cell distribution width during the last years of life in geriatric patients

Abstract: In our cohort of geriatric patients, RDW is a dynamic variable that is modified during the last five years of life, irrespective of their age, and especially during the last year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, until now, anemia has not been generally acknowledged as a biomarker for advanced age. A Spanish study group 52 showed a significant association between the anemia-associated parameter red cell distribution width (RDW) and mortality, with RDW rising during the last 5 years of life. Elevated RDW levels, reflecting an increase of anisocytosis, have been shown to be associated with chronic diseases 53 and chronic inflammation.…”
Section: Association Between Anemia Frailty and Inflammagingmentioning
confidence: 99%
“…However, until now, anemia has not been generally acknowledged as a biomarker for advanced age. A Spanish study group 52 showed a significant association between the anemia-associated parameter red cell distribution width (RDW) and mortality, with RDW rising during the last 5 years of life. Elevated RDW levels, reflecting an increase of anisocytosis, have been shown to be associated with chronic diseases 53 and chronic inflammation.…”
Section: Association Between Anemia Frailty and Inflammagingmentioning
confidence: 99%
“…A significant association between the anemia-associated parameter red cell distribution width (RDW) and mortality is already found. RDW is rising during the last 5 years of life and elevation of RDW levels has been shown to be associated with chronic diseases and chronic inflammation 5,6 .…”
mentioning
confidence: 99%